Copper ore cargo on dock at Cordova, ca. 1912 - Thwaites, John E. (John Edward), 1863-1940 (1912)
Caption on image: Dock at Cordova, Alaska, covered with copper ore. Value $46 per sack PH Coll 247.528 Cordova is located at the southeastern end of Prince William Sound in the Gulf of Alaska. The community was built on Orca Inlet, at the base of Eyak Mountain. It lies 52 air miles southeast of Valdez and 150 miles southeast of Anchorage. The area has historically been the home to Aleuts, with the addition of migrating Athabascan and Tlingit natives who called themselves Eyaks. Alaskan Natives of other descents also settled in Cordova. Orca Inlet was originally named "Puerto Cordova" by Don Salvador Fidalgo in 1790. One of the first producing oil fields in Alaska was discovered at Katalla, 47 miles southeast of Cordova, in 1902. The town of Cordova was named in 1906 by Michael Heney, builder of the Copper River and Northwestern Railroad. Cordova became the railroad terminus and ocean shipping port for copper ore from the Kennecott Mine up the Copper River. The first trainload of ore was loaded onto the steamship "Northwestern," bound for a smelter in Tacoma, Washington, in April 1911. The Bonanza-Kennecott Mines operated until 1938 and yielded over $200 million in copper, silver and gold. The Katalla oil field produced until 1933, when it was destroyed by fire. Fishing became the economic base in the early 1940s. Cordova was the railroad terminus and ocean shipping port for copper ore from the Kennecott Mine up the Copper River.